Curious George goes camping - Rey, Margret; Shalleck, Alan J. (Boston : Houghton Mifflin, 1990)
Curious George gets into mischief while camping but is able to redeem himself in an emergency.
Cover title: Margret and H.A. Rey's Curious George goes camping.
"Adapted from the Curious George film series."
"Sandpiper Houghton Mifflin books"--P. [4] of cover.
Keywords: Monkeys -- Fiction; Camping -- Fiction